Exponential model for analysis of heart rate responses and autonomic cardiac modulation during different intensities of physical exercise. Issue 10 (16th October 2019) - Silva, Lucas Raphael Bento; Gentil, Paulo Roberto Viana; Beltrame, Thomas; Basso Filho, Marco Antônio; Alves, Fagner Medeiros; Silva, Maria Sebastiana; Pedrino, Gustavo Rodrigues; Ramirez-Campillo, Rodrigo; Coswig, Victor; Rebelo, Ana Cristina Silva
Abstract : The aim of this study was to compare the heart rate (HR) dynamics and variability before and after high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) protocols with workloads based on treadmill workload at which maximal oxygen uptake was achieved ( WL V ˙ O 2 max ) . Ten participants performed cardiopulmonary exercise testing (CPET) to obtain oxygen uptake ( WL V ˙ O 2 max ) . All training protocols were performed on a treadmill, with 0% grade, and had similar total distance. The MICT was composed by 21 min at 70% of WL V ˙ O 2 max . The first HIIT protocol (HIIT-30 : 30) was composed by 29 repetitions of 30 s at 100% of s V ˙ O 2 max and the second HIIT protocol (HIIT-4 : 3) was composed by three repetitions of 4 min at 90% of WL V ˙ O 2 max . Before, during and after each training protocol, HR dynamics and variability (HRV) were analysed by standard kinetics and linear (time and frequency domains). The repeated measures analysis of variance indicated that the HR dynamics, which characterizes the speed of HR during the rest to exercise transition, was statistically ( p < 0.05) slower during MICT in comparison to both HIIT protocols. The HRV analysis, which characterizes the cardiac autonomic modulation during the exercise recovery, was statistically higher in HIIT-4 : 3 in comparison to MICT and HIIT-30 : 30 protocols ( p < 0.005 and p = 0.012, respectively), suggesting that the HIIT-4 : 3 induced higher sympathetic and lower parasympathetic modulation during exercise in comparison to the other training protocols. In conclusion, HIIT-4 : 3 demonstrated post-exercise sympathetic hyperactivity and a higher HRpeak, while the HIIT-30 : 30 and MICT resulted in better HRV and HR in the exercise-recovery transition. The cardiac autonomic balance increased in HIIT-30 : 30 while HIIT-4 : 3 induced sympathetic hyperactivity and cardiac overload.